Harming Democracy in Mediolatry Societies: Decoding the Marketing of War and Animosities through Photo Images - Gouliamos, Kostas; Theocharous, Antonis L. (My University, 2008)
History can reveal a continuous stream of conflict, enmity, and violence. A general review of the world political scene presents an amalgam of stable and unstable countries/regions where acts of violence and conflict have been interwoven with the political lifeworld. Photo images are a powerful medium that greatly influences the interpretation of past events and the understanding of history. People often learn about events after they occur and depend either on social imagery (Newman, 1999) or on photography to construct cognitive frameworks about the past (Burke, 2001; Rose, 2001). Through the application of a symbolic interactionism methodological framework (Denzin, 1992), this paper explores how opinion leaders/decision makers perceive, understand, and interpret past political events as they are portrayed by photo images found in the international press. The interviewing and conversational analysis that has been adopted has allowed the comparison of the perspectives/interpretations given by the participants, something that ultimately has led to the extraction of conclusions on how people from different functions of democracy apparatus construct cognitive frameworks of political events according to their professional background. The imposition of mediolatry by “marketing war” or/and “packaging politics” denominators has encouraged the mobilization of democratic participation, while on the other hand, it has cultivated political cynicism about politicians' decisions or actions. The paper, through a qualitative approach and critical analysis, formulates two models that apprehend the generative process of terrorism, war, intervention, and ethnic cleansing, a process that undoubtedly harms modern democracy.
Keywords: Animosities; Geopolitics; Marketing of war; Mediolatry; Neo-corporatism and democracy; Packaging politics; Photo images; Political marketing/communication